Turnaround in response to extreme financial shocks: case studies of National Governing Bodies of Sport (NGB's) in the UK - Bostock, J.; Breese, R.; Ridley-Duff, R. (2016)
The research explores the turnaround strategies employed by National Governing Bodies for Sport (NGB) in response to them receiving significant reductions in their funding from UK Sport (the body responsible for elite sport in the UK) after the London Olympic Games in 2012. It seeks to analyse the consequences of these measures on strategic direction. By exploring the impacts of the funding reductions on the NGBs, this research seeks to explore critical examples of how sport organisations can purposefully respond to a significant change in their environment, in this case a severe financial shock, through enacting a turnaround strategy. The research has wider implications for the analysis of turnaround situations beyond the sporting context.